2017
DOI: 10.1159/000452417
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Opioid System and Personality Traits Using Positron Emission Tomography

Abstract: Background: Personality traits, such as Neuroticism and Extraversion, have been implicated in the processing of emotion. The neural correlates most often associated with Neuroticism and Extraversion are the insular cortex, orbitofrontal cortex, amygdala, and ventral striatum. Objective: The aim of the current study was to explore neurotransmitter systems underlying those neural correlates and investigate the relationship between personality traits and opioid receptor binding potential. Method: Twelve healthy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…These findings are congruent with neuropsychological data indicating that neuroticism is linked to a negative bias in attention, a negative bias in interpretation and recall of information, as well as increased reactivity and poor coping 41 . Neuroticism has also been linked to increased opioid receptor binding in the right anterior insula 42 . Links to fronto-amygdala activity in harm avoidance have also been noted 43 …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These findings are congruent with neuropsychological data indicating that neuroticism is linked to a negative bias in attention, a negative bias in interpretation and recall of information, as well as increased reactivity and poor coping 41 . Neuroticism has also been linked to increased opioid receptor binding in the right anterior insula 42 . Links to fronto-amygdala activity in harm avoidance have also been noted 43 …”
Section: Resultssupporting
confidence: 78%
“…41 Neuroticism has also been linked to increased opioid receptor binding in the right anterior insula. 42 Links to frontoamygdala activity in harm avoidance have also been noted. 43,44 fMRI work on avoidance in healthy adults found increased activation of the nucleus accumbens (NAcc) in active avoidance and enhanced deactivation during passive avoidance.…”
Section: Neuroimagingmentioning
confidence: 95%
“…In an American PET study with [ 11 C]DPN in 12 healthy subjects, a high score of neuroticism was found to be associated with high opioid receptor binding in the right anterior insula. On the other hand, a high score of extraversion was associated with low tracer binding in the left posterior insula (Rodman et al 2017).…”
Section: Personality Traitsmentioning
confidence: 91%
“…Genetic studies in conditions related to narcissism (e.g. antisocial or borderline personality disorders) (Caspi et al, 2008;Langley et al, 2010;Silberschmidt & Sponheim, 2008) and imaging studies on the relationship of monoamine or opiate receptor binding to dimensional personality measures (Breier et al, 1998;Caravaggio et al, 2017;Farde et al, 2018;Moresco et al, 2002;Rodman et al, 2017) have provided significant evidence for the existence of specific biological correlates of personality disorders and the quantitative expression of personality dimension. In order to explore new ways of thinking about narcissism, we searched for pharmacological models that could inform future research into the neurobiology of narcissism.…”
Section: Introductionmentioning
confidence: 99%